2015
DOI: 10.1007/s00464-015-4335-2
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of a randomized controlled trial of T2 versus T2–T3 ablation in endoscopic thoracic sympathectomy for palmar hyperhidrosis

Abstract: There was no difference in recurrence rates and CH between single-level (T2) and multi-level (T2-T3) ETSs in the long term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…CS is greater with T2-T4 resection than with T2 or T3 only or T2-T3 resection [17]. Limitation of the denervation level is the most commonly used method to decrease the incidence of complications and achieve satisfactory results [18][19][20]. The HDSS proofs a valuable asset for patient selection and quantification of the perceived severity of hyperhidrosis.…”
Section: Discussionmentioning
confidence: 99%
“…CS is greater with T2-T4 resection than with T2 or T3 only or T2-T3 resection [17]. Limitation of the denervation level is the most commonly used method to decrease the incidence of complications and achieve satisfactory results [18][19][20]. The HDSS proofs a valuable asset for patient selection and quantification of the perceived severity of hyperhidrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional TS at the T2–T3 or T2–T4 levels can improve the symptoms of PH well but also increases the risk of postoperative complications (such as CS and dry hands) 35 . Limitation of the denervation level is the most commonly used method to decrease the incidence of complications and achieve satisfactory results 68 . In recent years, TS at a single level rather than at multiple levels is increasingly preferred.…”
Section: Discussionmentioning
confidence: 99%
“…Various methods have been tried to decrease the incidence of complications after TS, and limitation of the extent of surgical dissection has been found to be the key to achieving this goal. Several authors have performed TS at a single level and achieved a better curative effect (similar resolution of symptoms and lower incidence of CS) than that achieved with TS at multiple levels 68 . With the deepening of our understanding of TS, single-level surgeries, especially at the T3 or T4 level, became increasingly common.…”
Section: Introductionmentioning
confidence: 99%
“…The most important side effect of sympathectomy is compensatory sweating [ 9 12 ]. Various studies have found controversial results regarding this side effect, which is reported to have developed in 3% to 98% of the cases [ 12 ]. In our series, compensatory sweating developed in 32 (34.7%) patients.…”
Section: Discussionmentioning
confidence: 99%
“…In our series, compensatory sweating developed in 32 (34.7%) patients. It was located mostly at the back, chest and abdominal area [ 9 12 ]. We did not observe any difference in the results for compensatory sweating with regard to the sympathicotomy level ( p = 0.759).…”
Section: Discussionmentioning
confidence: 99%